Web 2.0 and beyond : principles and technologies - Anderson, Paul (Paul David), 1964- (Boca Raton : CRC Press, 2012)
'Preface The Web is no longer the sole preserve of computer science. Web 2.0 services have imbued the Web as a technical infrastructure with the imprint of human behaviour, and this has consequently attracted attention from many new fields of study including business studies, economics, information science, law, media studies, philosophy, psychology, social informatics and sociology. In fact, to understand the implications of Web 2.0, an interdisciplinary approach is needed, and in writing this book I have been influenced by Web science--a new academic discipline that studies the Web as a large, complex, engineered environment and the impact it has on society. The structure of this book is based on the iceberg model that I initially developed in 2007 as a way of thinking about Web 2.0. I have since elaborated on this and included summaries of important research areas from many different disciplines, which have been brought together as themes. To finish off, I have included a chapter on the future that both draws on the ideas presented earlier in the book and challenges readers to apply them based on what they have learned. Readership The book is aimed at an international audience, interested in forming a deeper understanding of what Web 2.0 might be and how it could develop in the future. Although it is an academic textbook, it has been written in an accessible style and parts of it can be used at an introductory undergraduate level with readers from many different backgrounds who have little knowledge of computing. In addition, parts of the book will push beyond the levels of expertise of such readers to address both computer science undergraduates and post-graduate research students, who ought to find the literature reviews in Section II to be'--
'Chapman & Hall book'
Includes bibliographical references and index.
Keywords: Web 2.0.; Internet -- Social aspects